The impact of digital household budgets on online purchase decision-making processes - Florian Skwara; Luca Wienert (Journal of Consumer Behaviour, 2023)
Recent literature found positive effects of digital household budget feedback when used over longer timespans. This current study, in turn, investigates whether digital budget feedback also influences consumer behavior in single online purchase decisions. The related research question states: Do transparent technology-mediated household budgets influence consumers' willingness to pay and payment pain in single, individual online purchase decision processes? The underlying study used a quantitative-, mixed-design approach and simulated online purchases for one hedonic and one utilitarian product. Three hundred fourteen study subjects were assigned to either a control group or one of three treatment groups manipulated with specific budget statuses to examine differences in consumer reactions. Critical measures of willingness to pay and payment pain have been taken to analyze potential significant effects. Results found significant differences in consumer willingness to pay and payment pain between and within groups concerning both products. The study could, however, not confirm differences to occur between utilitarian and hedonic purchases. The findings extend existing literature by demonstrating that consumers adjust their online spending based on individual household budget feedback. Consumers that wish to align spending with their current budget status might thus rely on app-mediated budget updates. At the same time, marketers could offer individualized pricing offers to consumers based on situational budget status information.
Keywords: 320